Valve-Sparing Operation in Patients with Aortic Root Aneurysm - Tsvyk, A. S.; Dovgan, A. M.; Varbanets, S. V.; Payuk, V. V.; Pukas, A. Y. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Aortic root aneurysm is rare but life-threatening disease which affects not only aortic wall, but aortic valve as well. Valve-sparing operation was developed by Tirone David and gave a chance to save native aortic valve in patients with aortic root aneurysm and to avoid aortic valve replacement. The aim. To analyze postoperative results and complications after aortic valve-sparing operation in patients with aortic root aneurysm. Materials and methods. Sixteen patients with aortic root aneurysm were operated at the Ukrainian Children’s Cardiac Center (UCCC) during the period from 2012 to 2018. The patients underwent aortic root reimplantation. Results. Postoperative results were analyzed in 100% cases. Mean postoperative follow-up period was 25.6 ± 13.3 months. Total mortality was 0%. No patients required re-operation due to aortic aneurysm or that on aortic valve. Conclusions. Collected data indicates that aortic root reimplantation is the procedure which can be chosen both for young and old patients. This is the procedure with lower risks and mortality comparing to aortic root replacement. It gives chance to preserve native aortic valve and its adequate functioning. Postoperative observation results indicate long-term freedom from reoperation due to aortic aneurysm and aortic valve insufficiency. This procedure is equally efficient in patients with either tricuspid or bicuspid aortic valve and can be efficiently implemented in patients with Marfan syndrome.